PENYULUHAN HUKUM PELAPORAN PENERIMAAN SUMBANGAN DANA KAMPANYE SEBAGAI KONVENSI KETATANEGARAAN PEMILU - Indra Lorenly Nainggolan; Nina Zainab; Jantarda Mauli Hutagalung (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Reporting on campaign funds is an order regulated inLaw No. 7 of 2017. Campaign funds come from political parties,candidates for Regency/Municipal Regional People'sRepresentative Assembly members, including contributions thatare legal under the law. There is no regulation for reportingcampaign fund contributions obtained from other parties. The2014 and 2019 elections have KPU regulations governing them.Specifically for the 2024 elections, implementing regulationshave not yet been formed. In the absence of regulation, this actionis not consistent with the previous election and will give rise tothe potential for election violations. The partner of this serviceactivity is bekasi election monitoring body. Participants inservice activity were faced with the problem of whether it wasnecessary to report campaign funds contributions from otherparties and what the legal basis was. This service activity offersa solution that the KPU should still make implementingregulations regarding reporting of campaign fund donationsobtained from other parties. The argument is that the electionsconstitutional conventions for the 2014 and 2019 electionsregulate these provisions and the consequences of Article 334paragraph 2 of Law No. 7 of 2017.